Ekspresi Reseptor Estrogen, Reseptor Progesteron Dan Digit Ratio Pada Pasien Meningioma - Prakoso, Teguh Iman; Arifin, Mohammad Thohar; Sadhana, Udadi; Puspasari, Dik; Kusuma Astuti, Meira Dewi (RSUP Dr. Kariadi, 2020)
Latar belakang Meningioma merupakan tumor jinak intrakranial primer yang dipengaruhi oleh keseimbangan hormon estrogen dan progesteron. Digit Ratio (2D : 4D) sangat dipengaruhi oleh paparan hormon androgen prenatal khususnya estrogen dan testosteron. Tujuan Mengetahui hubungan reseptor estrogen (ER) dan reseptor progesteron (PR) dengan Digit Ratio (2D : 4D) pada pasien meningioma. Metode Penelitian observasional analitik dengan desain cross sectional study. Jumlah sampel sebesar 25 pasien meningioma yang dilakukan pemeriksaan ER dan PR. Pengukuran Digit Ratio dilakukan di poliklinik dan bangsal bedah syaraf RSUP Dr. Kariadi Semarang. Uji statistik menggunakan uji spearman. Hasil Digit Ratio kanan, kiri dan selisih kanan-kiri dengan nilai rerata 1,0046; 1,0021 dan 0,0492. Uji spearman, hubungan Digit Ratio kanan, Digit Ratio kiri dan Selisih Digit Ratio kanan kiri dengan PR didapatkan masin–masing nilai p = 0,5 (r = 0,1), p = 0,8 ( r = 0,1), dan p = 0,3 (r = 0,2). Hubungan Digit Ratio kanan, Digit Ratio kiri dan Selisih Digit Ratio kanan kiri dengan ER didapatkan masing–masing nilai p = 0,4 (r = 0,2), p = 0,5 ( r = -0,1), dan p = 0,9 (r = 0,1). Secara statistik terdapat hubungan yang sangat lemah antara Digit Ratio kanan, Digit Ratio kiri, selisih Digit Ratio kanan kiri dengan ER dan PR pada pasien meningioma Simpulan Terdapat hubungan yang sangat lemah antara reseptor estrogen (ER) dan reseptor progesteron (PR) dengan Digit Ratio pada pasien meningioma. Kata kunci : Reseptor Estrogen, Reseptor Progesteron, Digit Ratio, Meningioma. Background Meningiomas are primary intracranial benign tumors that are affected by the balance of estrogen and progesterone. Digit Ratio (2D: 4D) is strongly influenced by exposure to prenatal androgen hormones especially estrogen and testosterone. Objective To determine the relationship between estrogen receptor (ER) and progesterone receptor (PR) with Digit Ratio (2D: 4D) in meningioma patients. Method Analytical observational research with cross-sectional study design. The total sample of 25 meningioma patients who underwent ER and PR examinations. Digit Ratio measurements were performed at the clinic and neurosurgical ward of RSUP Dr. Kariadi Semarang. The Spearman test was used for the statistical test. Results Right, left and right-left difference digit ratio with mean value of 1.0046; 1,0021 and 0,0492. After Spearman test, the relationship between right Digit Ratio, left Digit Ratio and Difference between right and left Digit Ratio with PR was p = 0.5 (r = 0.1), p = 0.8 (r = 0.1), and p = 0.3 (r = 0.2). Correlation between right Digit Ratio, left Digit Ratio and Difference between left and right Digit Ratio with ER was p = 0.4 (r = 0.2), p = 0.5 (r = -0.1), and p = 0.9 (r = 0.1). Statistically there is a very weak relationship between right Digit Ratio, left Digit Ratio, difference between right and left Digit Ratio with ER and PR in patients with meningiomas. Conclusions There is a very weak relationship between estrogen receptors (ER) and progesterone receptors (PR) and Digit Ratio in meningioma patient. Keywords: Estrogen Receptor, Progesterone Receptor, Digit Ratio, Meningioma.